Learning approaches in accounting education: towards deep learning - Lau, Yeng Wai; Lim, Shi Yee (Growing Science, 2015)
Deep learning facilitates development of generic skills pertinent to prepare graduates for employment. Accounting education with syllabuses burdened with accounting standards to be memorized and regurgitated in examinations does little to promote deep learning. This study conducted a questionnaire survey to examine the extent to which accounting undergraduates at a public university in Malaysia adopt deep learning. This study demonstrates that deep learning is not readily attainable. Surface learning, which promotes rote memorization, constitutes a stepping stone towards deep learning. Having a preference or thirst for meanings is also pertinent to motivate undergraduates to move from rote memorization to seek meanings and thus deep learning. Female undergraduates have been found to be more inclined to adopt deep learning. Much is still to be learned on how best to promote deep learning as learning is a life-long process where everyday life experiences, both on and off-campus, facilitate learning and development.